Decomposition dynamics of soybean residues in two soils of different fertility - Luiza Tavares, Rose; Nahas, Ely (Science Alert, 2013)
The study objective was to evaluate the influence of the addition of soybeans residues on the chemical properties of Eutrudox and Hapludox soils. Soybean leaves and stems were incubated for 0-200 days. The statistical model used was a 5×4 factorial (plantxincubation period) with three replications. Soils without addition of plants were used as controls. Total Organic Carbon (TOC), Soluble Carbon (SC), Total Carbohydrates (TC), Humic Acid (HA), Fulvic Acid (FA) and Humification Rate (HR) were determined. Higher values of chemical attributes (TOC, SC and TC) were found in the Eutrudox soil than in the Hapludox soil and these values increased significantly (p<0.05) after 50 days of incubation in relation to the initial period. The TOC, SC and TC increased in soils amended with soybean plants when compared to controls without plants. HA and FA contents and HR were not affected by the addition of soybean residues. Maximum HA contents were found after 100 days and maximum FA contents and HR were found after 200 days incubation in both soils. It can be concluded that the addition of soybean residues increased the soil chemical properties when compared to the controls. © 2013 Academic Journals Inc.
Keywords: Fulvic acid; Humic acid; Humification rate; Soluble carbon; Total carbohydrates; Total organic carbon